INDONESIAN LANGUAGE AND ARTS - ERNITA DAULAY (VISION, 2016)
Indonesia is culturally rich. Indonesian art and culture are intertwined with religion and age-old traditions from the time of early migrants with Western thoughts brought by Portuguese traders and Dutch colonists.The culture of Indonesia has been shaped by long interaction between original indigenous customs and multiple foreign influences.In addition to these basic cultural sensitivities, religion plays a large role in Indonesian life and values. Over eighty-five percent of the people in Indonesia consider themselves Muslims, though their practices differ considerably from Islam as it's practiced in the Middle East. This is because of the rich texture of different religious traditions in the archipelago, from Buddhism and Hinduism to Chinese Confucianism to European Christianity to indigenous animist and ancestor worship practices. For many, the name of Islam is only the sheet that covers the shape of their ancestors' and communities' eclectic spiritual practices. The islands of Indonesia have been major trade hubs for over a thousand years, and each island has its own unique mix of religious traditions and practices depending on who decided to set port there. Therefore, while there are a few religious and spiritual practices that are practiced by a majority of the population, the main rule regarding religion in Indonesia is,"Judge not, lest ye be judged."? By and large, Indonesians are very friendly people, always willing to strike up a conversation and interested in connecting with foreigners. This can seem extreme to some travellers, particularly for those from Western cities where just looking at someone in the subway can be cause for angry glares.The arts of Indonesia are many, especially Indonesian paintings which are unique works of art. Indonesian culture, especially its architecture has been to a great extent dominated and influenced by the Indian, although European influences have also been particularly strong since the nineteenth century. Traditional buildings in Indonesia are built on stilts with oversized saddle roofs which have been the home of the Batak and the Toraja.Key words: Indonesian Tradition, Indonesian Arts and Language and People